The Influence of Digital Competencies and AI Integration on Islamic Teachers’ Functional Skills in Southern Pakistan - Muhammad Kashif Majeed; Tunku Badariah Binti Ahmad (Indo Green Journal, 2026)
In this study, we investigate digital competencies and their interaction with AI in Islamic secondary schools of Southern Pakistan, as well as their impact on teachers’ functional skills. The integration of artificial intelligence and digital skills into the education process can address critical questions related to teacher performance and skill development. This quantitative study analyzes responses from a sample of 450 Islamic school teachers using SPSS 22, based on the study criteria. The impact of digital competencies and AI usage on functional teaching skills was evaluated using multiple linear regression.The results reveal that the use of AI tools did not significantly affect communication skills, as the significance value (0.073 > 0.05) exceeded the threshold. However, digital competencies had a significant influence on all functional skills, with a significance value of 0.000 < 0.05. These findings highlight the importance of digital skills in contemporary education and identify gaps in AI adoption among rural Islamic school teachers. This study contributes to understanding teacher digital readiness, AI adaptation, and professional skill enhancement. The insights provide recommendations for improving educational practices, technology integration policies, and teacher development programs in Southern Pakistan, offering valuable guidance for implementation in this context.